FERMENTATION OF SOYBEAN SEEDS USING RHIZOPUS OLIGOSPORUS FOR TEMPEH PRODUCTION AND STANDARDIZATION BASED ON ISOFLAVONES CONTENT - DWIATMAKA, YOHANES; YUNIARTI, NUNUNG; LUKITANINGSIH, ENDANG; WAHYUONO, SUBAGUS (International Journal of Applied Pharmaceutics, 2022)
Objective: To determine the best temperature and time of fermentation for making soybean (Glycine max (L.) Merril) tempeh seeds with high content of isoflavones. Methods: Five varieties of soybean seeds, Devon-1, Dena-1, Dega-1, Anjasmoro, and Argomulyo, were determined for their isoflavones content using an Ultraviolet (UV) spectrophotometer. A variety containing the highest isoflavones was washed, boiled, peeled, then mixed with tempeh starter (Rhizopus oligosporus culture) at 1 g/kg. The mixture was then poured into plastic bags and flattened with two centimeters of thickness. Fermentation in three conditions: (a) ambient temperature (27-32 °C) without air circulation, (b) 27±0.5 °C, and (c) 30±0.5 °C both with air circulation. The inner temperature, ripening time, and rotting time was recorded. The total isoflavones content was measured every 6 h. Results: The variety of Devon-1 has the highest content of isoflavones (0.112% w/w). Fermentation in condition (a) caused the tempeh too hot (42 °C) and rotted at the 42nd h. Condition (b) produced the best tempeh, ripening at the inner peak temperature (32.5 °C) at the 32nd h; and rotted after the 100th h. Condition (c) produced good tempeh; the ripening occurred at the 31st h at 33 °C and rotted after the 113th h. Tempeh that was produced with condition (b) at the 72nd h has the highest content of isoflavones (0.089% w/w). Conclusion: Fermentation at 27±0.5 °C with air circulation for 72 h produced tempeh with the highest isoflavones content (0.089% w/w), but decrease about 20% compared to its content in seeds (0.112% w/w).